Susceptibilidade à degradação/desertificação na sub-bacia hidrográfica do Riacho Feiticeiro (Ceará/Brasil) e na micro-bacia da Ribeira Grande (Santiago/Cabo Verde) - Sousa, Maria Losângela Martins de (2016)
This research aims to study the problem of desertification in semi-arid basins. The main goal is to evaluate the susceptibility to degradation/desertification in the subbasin of the Feiticeiro Stream, located in the State of Ceará, Brazil and in the subbasin of the Ribeira Grande, located in the Santiago Island, Cabo Verde. Geobiophysical and socioeconomic indicators of desertification were used. The specific objectives are showed below: a) identify and characterize the environmental systems in the both sub-basin of Feiticeiro Stream and in the sub-basin of Ribeira Grande. The scales compatible with the objectives and territorial proposed areas are used to this. b) to carry out the socioeconomic characterization of the Feiticeiro and Ribeira Grande populations, through the sampled data at the municipal level and of the member localities; c) Identify the conditions of degradation/desertification, through the geobiophysical and socioeconomic indicators of desertification. In relation to the theoretical methodological aspects, the research was developed according to the Geosystemic Theory. This theory using integrated landscape studies consider the interaction between the elements of ecological potential, biological exploration and human action. It is structured in two stages: In office the documentary research was carried out, data were sampled, geocartographic and satellite image survey and thematic mapping were made, and in the field the terrestrial truth recognition was made, the application of field records and interpretation of satellite images were carried out. The results showed that studied basins are susceptibility to desertification. The susceptibility levels range from moderate to high and they have as main causes the influence of climatic conditions, and especially of human activities, which use inadequate techniques. Among the main consequences of desertification are the environmental dynamics of the areas in focus and the worsening of the quality of life of the people that live there. It is hoped that these results showed in this research will serve as a model for the application of the indicators of desertification in other basins, with their due adaptations